2013
DOI: 10.1115/1.4023015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the Interaction Between Rim Seal and Main Annulus Flow in a Low Pressure Two Stage Axial Turbine

Abstract: The spoiling effects of rim seal flow are studied at the Large Scale Turbine Rig (LSTR) at Technische Universität Darmstadt. Detailed flow field measurements and efficiency measurements were performed for various ingress and egress setups and will be presented in this paper. Efficiency measurements show an efficiency decrease as the rim seal mass flow is increased. Five hole probe measurements upstream and downstream of the second stator row show that an increasing rim seal mass flow leads to an increased pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Accordingly, the hot streak is distorted, but its spatial extent does not increase significantly across the vane row. Flow tracing has been applied by Schrewe [10], Feiereisen et al [11] and Lefrancois et al [12] to study the propagation of purge flow in low pressure turbines. The results of the last-mentioned working group have been identified to be transferable to engine conditions (Boutet-Blais et al [13]).…”
Section: Tracing Of Turbomachinery Flowsmentioning
confidence: 99%
“…Accordingly, the hot streak is distorted, but its spatial extent does not increase significantly across the vane row. Flow tracing has been applied by Schrewe [10], Feiereisen et al [11] and Lefrancois et al [12] to study the propagation of purge flow in low pressure turbines. The results of the last-mentioned working group have been identified to be transferable to engine conditions (Boutet-Blais et al [13]).…”
Section: Tracing Of Turbomachinery Flowsmentioning
confidence: 99%
“…Moreover, the blockage effects of the swirled and non-swirled rim seal flows were similar, because the blockage effect was primarily a function of the rim seal flow rate. Schrewe et al 13 performed experimental analysis of the interaction between rim seal and main annulus flow in a low pressure two-stage axial turbine, and reported that the rim seal flow blockage led the mainstream between the hub and 20% span to decelerate and the mainstream between the 20% span and 90% span to accelerate. Jia and Liu 14 numerically investigated the effect of rim seal and pointed out that the rim seal flow induced the blockage effect which would decelerate the flow near the hub and accelerate the mainstream at high spanwise position.…”
Section: Introductionmentioning
confidence: 99%
“…McLean et al [17] investigated the injection effect of purge flow on the aerodynamic performance in a turbine, which found that velocity profile modification was related to the purge flow. Schrewe et al [18] performed an efficiency measurement and found an efficiency drop with the increase of rim seal mass flow rate in a two-stage low-pressure turbine. Zerobin et al [19,20] investigated the influence of four individual purge flows on the aerodynamic performance of turbine center frames with a 1.5-stage turbine test setup.…”
Section: Introductionmentioning
confidence: 99%